2011
DOI: 10.1016/j.ymssp.2010.06.010
|View full text |Cite
|
Sign up to set email alerts
|

The application of spectral kurtosis on Acoustic Emission and vibrations from a defective bearing

Abstract: a b s t r a c tThe application of Acoustic Emission (AE) technology for machine health monitoring is gaining ground as power tool for health diagnostic of rolling element bearing. This paper provides an investigation that compares the applicability of AE and vibration technologies in monitoring a naturally degraded roller bearing. This research is the first known attempt investigating the comparative effectiveness of applying the Kurtogram to both vibration and AE data from a defective bearing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
71
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(75 citation statements)
references
References 20 publications
1
71
0
Order By: Relevance
“…A value greater than 3 indicates peaks which are related to AE activities caused by defects in the signal. 13 However, false detections can occur when processing signals collected from wheel-bearings from in-service trains. These errors can be caused by impulses arising from random sources reducing the overall ability of TSK to detect bearing faults.…”
Section: Tskmentioning
confidence: 99%
See 1 more Smart Citation
“…A value greater than 3 indicates peaks which are related to AE activities caused by defects in the signal. 13 However, false detections can occur when processing signals collected from wheel-bearings from in-service trains. These errors can be caused by impulses arising from random sources reducing the overall ability of TSK to detect bearing faults.…”
Section: Tskmentioning
confidence: 99%
“…15 To determine the SK, the signal is passed through a set of band-pass filters and then the kurtosis values of the filtered signals are calculated. 13 …”
Section: Tskmentioning
confidence: 99%
“…They demonstrated that the subsurface crack initiation and propagation can be detected by a time and frequency domain acoustic emission analysis. Eftekharnejad et al [11] compared the applicability of the acoustic emission and vibration methods in monitoring a naturally degraded roller bearing. They described that the acoustic emission method was more sensitive in diagnosing incipient faults than the vibration method.…”
Section: Introductionmentioning
confidence: 99%
“…Babak Eftekharnejad et.at, studied the relation between acoustic emission and vibration methods for defect identification of naturally damaged bearing. In this Acoustic emission is more sensitive in detecting incipient damage in bearing [11]. Faris Elasha et al researched that the fault detection ability of the AE is based upon the elimination of noise and also in the identification of the higher impact energy frequency region [12].…”
Section: Introductionmentioning
confidence: 99%